Comparison of PCR methods for detection of Leishmania siamensis infection - Hitakarun, Atitaya (BioMed Central, 2014)
BACKGROUND: Leishmania siamensis, a newly identified species, has been reported as a causative agent of leishmaniasis in Thailand. This organism has been identified and genetically characterized using PCR techniques based on several target genes. However, the sensitivities and specificities of these methods for the diagnosis of L. siamensis infection have never been evaluated. METHODS: To evaluate the sensitivities and specificities of PCR methods to detect L. siamensis infection, PCR for different genetic markers, i.e., the small subunit ribosomal RNA region (SSU-rRNA), the internal transcribed spacer 1 region (ITS1), cysteine protease B (cpb), cytochrome b (cyt b), heat shock protein 70 (hsp70), the spliced leader mini-exon, and the triose-phosphate isomerase (tim) genes were compared. RESULTS: Both the ITS1-PCR and the SSU rRNA-PCR could detect promastigote of L. siamensis at concentrations as low as 0.05 parasites/μl or the DNA concentration at 2.3 pg/μl. Though the ITS1-PCR method only recognized 8 samples as positive, all of these could be assessed as true positive according to microscopic diagnosis and/or amplifying the results of the PCR and their sequencing, while other methods also produced false positive results. Compared with the ITS1-PCR method, the PCR amplified SSU-rRNA and cpb gene showed 100% sensitivity for the detection of L. siamensis in clinical specimens. The PCR amplified mini-exon and hsp70 gene also gave a high sensitivity of 87.5%. In contrast, the PCR methods for cyt b and tim gene showed low sensitivity. The PCR methods for cyt b, mini-exon and tim gene showed 100% specificity compared with the ITS1-PCR. CONCLUSION: As a result, the ITS1-PCR method is a suitable target for PCR-based detection of L. siamensis infection in clinical specimens due to its high sensitivity and specificity. The results of this study can be used for molecular diagnosis as well as in epidemiological studies of L. siamensis in affected areas.